Knowledge about, attitudes toward and acceptance and predictors of intention to receive the mpox vaccine among cancer patients in China: A cross-sectional survey - Jie Ding; Xing-Chen Liu; Jing Hong; Qing-Mei Zhang; Xiao-Wan Xu; Yi-Qun Liu; Chao-Qin Yu (Human Vaccines & Immunotherapeutics)
This study aimed to investigate the knowledge about, attitudes toward, and acceptance and predictors of receiving the mpox vaccine among Chinese cancer patients. Patients were selected using a convenience sampling method. A web-based self-report questionnaire was developed to assess cancer patients’ knowledge, attitudes, and acceptance regarding the mpox vaccine. Multivariate logistic regression analysis was used to determine predictors of acceptance of the mpox vaccine. A total of 805 cancer patients were included in this study, with a vaccine hesitancy rate of 27.08%. Approximately 66% of the patients’ information about mpox and the vaccine came from the mass media, and there was a significant bias in the hesitant group’s knowledge about mpox and the vaccine. Multivariable logistic regression analysis suggested that retirement; chemotherapy; the belief that the mpox vaccine could prevent disease, that vaccination should be compulsory when appropriate and that the mpox vaccine prevents mpox and reduces complications; the willingness to pay for the mpox vaccine; the willingness to recommend that friends and family receive the mpox vaccine; and the belief that the mpox vaccine should be distributed fairly and equitably were factors that promoted vaccination. The belief that mpox worsens tumor prognosis was a driving factor for vaccine hesitancy. This study investigated the knowledge of cancer patients about mpox and the vaccine, evaluated the acceptance and hesitancy rates of the mpox vaccine and examined the predictors of vaccination intention. We suggest that the government scientifically promote the vaccine and develop policies such as free vaccination and personalized vaccination to increase the awareness and acceptance rate of the mpox vaccine.